The Impact of Timing of Antiretroviral Therapy Initiation on Retention in Care, Viral Load Suppression and Mortality in People Living with HIV: A Study in a University Hospital in Thailand - Pruke Eamsakulrat (2022)
Studies investigating same-day antiretroviral therapy (ART) initiation demonstrate different clinical outcomes depending on settings. We retrospectively reviewed adults with newly positive human immunodeficiency virus (HIV) antibody testing. The proportion of individuals who were retained in care at 12 months was compared between early (≤2 weeks) and late (>2 weeks) ART initiation groups. Of all, the median (IQR) time from HIV diagnosis to ART initiation was 18 (9-30) days. This duration was 7 (7-13) days in the early ART initiation group (n = 116) and 28 (21-46) days in the late ART initiation group (n = 154). In the multivariate logistic regression, having pneumocystis pneumonia [odds ratio (OR) 9.30, 95% CI 2.56-33.75], tuberculosis (OR 2.21, 95% CI 1.03-4.73), and weight loss (OR 12.98, 95% CI 1.00-167.68) were associated with late ART initiation. The early ART initiation group had a slightly higher proportion of individuals retained in care at 12 months than those in the late ART initiation group (88.8% vs 80.5%, P =.066) and had a higher significant proportion of HIV viral load suppression (81.0% vs 70.1%, P =.041). No significant differences were observed in the proportion of individuals who died at 12 months (2.6% vs 3.2%, P = 1.000) between the two groups. Early ART initiation trends to retain individuals in care and higher HIV viral load suppression was determined. Nevertheless, ART initiation timing might not be a solely important factor in improving HIV care and minimizing mortality among HIV-infected individuals in a university hospital setting.